A script for change: Using theatre to facilitate difficult conversations about graduate supervision - Cox, Susan; Smithdeal, Matthew; Lee, Michael (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2025)
Graduate supervision profoundly impacts graduate student, faculty, and staff wellbeing. Tensions within supervisory relationships are further complicated by equity and inclusion related barriers facing marginalized communities within academia. To address this situation, we created Rock the Boat, an open access educational resource that uses Research-based Theatre to provoke dialogue about supervisory relationships. Rock the Boat includes four professionally acted scenes plus a facilitator’s guide and supplementary resources. Our online piloting process supports the effectiveness of Rock the Boat in generating dialogue and enhancing perspective-taking, empathy, and reflective practice among participants. This paper offers a narrative review of the process of creating Rock the Boat, detailing many decisions made during the transition from live theatre workshops to film and online discussion.